Testing modified (Horndeski) gravity by combining intrinsic galaxy alignments with cosmic shear - Reischke, Robert; Bosca, Victor; Tugendhat, Tim; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2022)
We study the impact of modified gravity of the Horndeski class on intrinsic shape correlations in cosmic shear surveys. As these correlations intrinsic alignments are caused by tidal gravitational fields acting on galaxies as a collection of massive non-relativistic test particles, they are only sensitive to the gravitational potential, which forms in conjunction with the curvature perturbation. In contrast, the cosmic shear signal probes the sum of these two, i.e. both Bardeen potentials. Combining these probes therefore constitutes a test of gravity, derived from a single measurement. Focusing on linear scales and alignments of elliptical galaxies, we study the impact on inference of the braiding $\hat{α }_{\rm B}$ and the time evolution of the Planck mass $\hat{α }_{\rm M}$ by treating IAs as a genuine signal contributing to the overall ellipticity correlation. We find that for euclid, IAs can help to improve constraints on modified gravity of the Horndeski-class by 10 per cent if the alignment parameter needed for the linear alignment model is provided by simulations. If, however, the IA needs to be self-calibrated, all of the sensitivity is put into the inference of the alignment strength D since there is a very strong correlation with the evolution of the Planck mass. Thus, diminishing the benefit of IA for probing modified gravitational theories. While this paper shows results mainly for modified gravity parameters, similar deductions can be drawn for the investigation of anisotropic stresses, parametrized modifications to the Poisson equation, the phenomenology of gravitational slip and to breaking degeneracies in a standard cosmology.
Gesehen am 21.04.2022